Innovative Approach in Teaching Graph Theory (International Journal of Scientific Research and Management (IJSRM), 2021)
Learners tend to get bored in learning Graph Theory and this results them getting low performance. Thus, this study was conducted to find empirical evidence on the attempt of having an innovative approach in teaching graph theory through the utilization of games to college students. This study was a pre - experimental research in which pretest-post test was used. Moreover, it also utilized a qualitative research method to find out learners’ feedback on the approach. The learners have their permanent group assignment and games were utilized for every topic. Pretest and post test were administered. The test scores were recorded, tabulated, analyzed and interpreted. Data were analyzed using paired-sample t-test. Results revealed a highly significant difference from pretest to post test of the students. Additionally, students give positive feedback on the attempt of this innovative approach in teaching graph theory. Such that, the following are some of their response: “I am excited to study graph theory because of games”, “I look forward to games every meeting”, etc. Therefore, college students exposed to games while learning shows very high knowledge in Graph Theory.